Biofilm formation of food borne pathogens on plastic surfaces: An in situ and ex situ evaluation - Neeksha Naik; Saloni Prabhakar; Ballamoole Krishna Kumar; Ramya Harsha (Food and Humanity, 2026)

System dynamics modelling of India’s net zero transition - Ramya Natarajan; Aparna Sundaresan; Kaveri Ashok; Anasuya Gangopadhyay; Divya Davis; Krithika Ravishankar; Sweta Bhushan; Sarah Khan; Kunal Jagdale; Upasna Ranjan; Chandrakiran L; Indu K Murthy; et al. (Energy and Climate Change, 2026)

Nickel-olivine catalyst action and supercritical water gasification processing of municipal waste for hydrogen extraction - Madaminov Sanjarbek Maxmudjon Ugli; Pradeep Kumar Singh; G. Tejasri Devi; Himanshu Makhija; P.S. Ranjit; Manish Nagpal; Ponmurugan Panneerselvam; Ramya Maranan; Anand Rajendran; M. Murali (Biomass and Bioenergy, 2026)

Functional Cardiac Biomaterials: Insights into Constructing a Vascularized Myocardial Tissue Surrogate - Suresh Kumar Saravanan; Ramya Ramadoss; Pavithra Velmurugan; Veni Subramanyam; Balasubramanian Moovarkumudalvan (Cardiovascular Engineering and Technology, 2026)

Evaluating PM2.5 acidity using thermodynamic models and source contributions in Eastern India - Abisheg Dhandapani; Jawed Iqbal; Radhakrishnan Naresh Kumar; Delwin Pullokaran; Diksha Haswani; Deeksha Shukla; Ramya Sunder Raman (Environmental Monitoring and Assessment, 2026)

Integrative metrics for ecosystem health: development and application of a multimetric assessment framework - Vijayakumar Leela Ramya; Jesna Parakkandi; Ajoy Saha; Sajina AM; Vijaykumar Muttanahalli Eregowda; Basanta Kumar Das (Environmental Monitoring and Assessment, 2026)

Evaluation of MERRA-2 PM2.5 species at three locations in India and their historical (1999–2019) trends - Sandeep Devaliya; Sayak Patra; Prem Maheshwarkar; Ankur Bhardwaj; Diksha Haswani; Deeksha Shukla; Ramya Sunder Raman; Abisheg Dhandapani; R. Naresh Kumar; Jithin K. P.; Lokesh Kaggere (Environmental Monitoring and Assessment, 2026)

Photocatalytic dye degradation under natural diurnal sunlight using anatase TiO2 nanorods: A structure-performance study - Prathima Tanguturi Venkata; Anil Kumar Reddy Police; Jungho Lee; Nagaveni Munnelli; Lakshmi Padma; Sulochana Thummala; Lakshmana Reddy Nagappagari; Ramya Parthasarathy; Cheralathan Kanakkampalayam Krishnan; Sakar Mohan; Chinna Gangi Reddy Nallagondu; Mamatha Kumari Murikinati; et al. (Journal of Water Process Engineering, 2026)

Colistin-induced acute kidney injury in neonates with sepsis and its association with plasma colistin concentration: a prospective cohort study - Ramya Kagnur; Kanya Mukhopadhyay; Nusrat Shafiq; Ritika Kondel Bhandari; Jogender Kumar; Avaneesh Kumar Pandey (European Journal of Clinical Pharmacology, 2026)

The Complete Mitochondrial Genome of Indigenous Catfish Mystus gulio: Shotgun Assembly, Insight into Structural Characterization and Phylogenetic Relationships - Suvra Roy; Pranaya Kumar Parida; V. L. Ramya; Dibakar Bhakta; Vikash Kumar; Bijay Kumar Behera; Basanta Kumar Das (Agricultural Research, 2026)

Impact of insect growth regulators on beneficial insects: a comprehensive review - Mohammad Ikram; M. R. Srinivasan; A. Suganthi; V. R. Saminathan; J. Auxcilia; M. Jayakanthan; Bimal Kumar Sahoo; Sivasankari Sivakumar; K. Kiruthika; A. R. Ramya; V. Deva Dharshini (Journal of Plant Diseases and Protection, 2026)

Morphological and molecular identification of pod borer complex infesting chickpea and their associated natural enemies - Doddachowdappa Sagar; Suresh Mahadev Nebapure; Ramya Ramesan Syamala; Rahul Kumar Chandel; Pathour Rajendra Shashank (International Journal of Tropical Insect Science, 2026)

A comprehensive review of secondary metabolites of the plant genus Ambrosia - Shravan Kumar Gunda; Venkata Aditya Duvvuri; Ramya Cheriyala (Phytochemistry Reviews, 2026)

Wind direction dominates the transport and deposition of fire proxies in tropical dry forest landscapes of the Western Ghats - Prabhakaran Ramya Bala; Kumar Nithin; Diptimayee Behera; Ambili Anoop; Binisia Sanatan; Velu Vinoj; Raman Sukumar (Global and Planetary Change, 2025)

Perilla leaf extract as a functional feed additive enhances immunity and AHPND resilience in shrimp - Athiya Azzahidah; Ramya Kumar; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

Genome characterization and pathogenesis of translucent post-larvae disease in white shrimp - Ramya Kumar; Athiya Azzahidah; Yik How Teoh; Chu-Fang Lo; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Mechanical and Structural Characterization of Curauá Fiber, Sugarcane Biochar, and Poly(Lactic Acid) Hybrid Green Composites for Sustainable Biomass Utilization - Velmurugan Ganesan; Jasgurpreet Singh Chohan; Kumar Gengappan; Prabhu Paramasivam; Ramya Maranan; Natrayan Lakshmaiya; Suresh Kumar Shanmugam (Sugar Tech, 2025)

Seed Priming Alters the Microbial Community Composition in Seedlings of Rice (Oryza sativa L.) - S. Ramya; Babanpreet Kour; K. Sudheer; M. B. Arun Kumar; Balasubramanian Ramakrishnan (Journal of Plant Growth Regulation, 2025)

Harnessing the agro-morphological potential of wild Lathyrus accessions conserved in the National Genebank of India - Rinky Resma Panda; Padmavati G. Gore; Jyoti Kumari; R. K. Pamarthi; Vandana Tyagi; Akanksha Singh; K. R. Ramya; R. K. Gautam; Shiv Kumar; G. P. Singh; Kuldeep Tripathi (Genetic Resources and Crop Evolution, 2025)

A comprehensive review of postharvest quality and non-thermal preservation techniques for functional mushrooms - N. Parvathy Nayana; C. S. Ramya; T. V. Arun Kumar; Pramod P. Aradwad; Anamika Thakur; Pramod Kumar Sahoo (Critical Reviews in Food Science and Nutrition, 2025)

Carbon-based nanofertilizers from marine biowaste: Innovations, applications, and sustainable nanoengineering strategies - M. Aruna; N. Nagabhooshanam; Rintu Kumar; Mamata Chahar; T. Sudhakar; N.B.C.S.N. Murthy; Ramya Maranan; M. Murali; S. Sathiyamurthy (Journal of Environmental Chemical Engineering, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

A multi-season analysis for GxE interactions and identification of resistant grape genotypes for powdery mildew (Erysiphe necator (Schw.) Burrill.) using AMMI, GGE and MTSI analysis - M. Ramya Sree; Sanjay K. Singh; Jai Prakash; Chavlesh Kumar; Gyan P. Mishra; Aundy Kumar; Amitha Mithra Sevanthi; R. Megha (Physiological and Molecular Plant Pathology, 2025)

Scientometric analysis of CF-PEEK composites: Research trends and emerging opportunities - Uppula Ramya; Pulla Sammaiah; K. Satheesh Kumar (Next Research, 2025)

A comparative analysis of machine learning approaches for predicting maturity in watermelon using acoustic and quality features - Parvathy Nayana N.; Arun Kumar T.V.; Pramod P. Aradwad; Achal Lama; Ritwika Das; Ramya C. S.; Mukesh Pattaiya; Utpal Ekka; Murtaza Hassan; Pramod Kumar Sahoo (Food Chemistry, 2025)

Bile acid- and taurocholate-mediated virulence in AHPND-causing Vibrio parahaemolyticus is independent of the LuxO-OpaR quorum sensing cascade - Ramya Kumar; Shin-Jen Lin; Chien-Kang Huang; Shih-Shun Lin; Hao-Ching Wang; Fernand F. Fagutao; Han-Ching Wang (Aquaculture, 2025)

Bacterial composition of dust deposited in Qatar: A seasonal study - Ramya Ramadoss; Adarsh Kumar Nishad; Balasubramanian Moovarkumudalvan; Basem Shomar (Science of The Total Environment, 2025)

Size-speciated chemistry of aerosols during the continental to marine air-mass transition phase from tropical Western Ghats environment in peninsular India - A.R. Aswini; Dhananjay Kumar Deshmukh; C.B. Ramya; Prashant Hegde; S. Suresh Babu (Atmospheric Research, 2025)

Microclimate determines the diversity patterns, biomass, and water storage capacity of bryophytes in the alpine ecosystem: a case study in Kashmir Himalaya - Ramya Ranjan Paul; Soumit Kumar Behera; Krishna Kumar Rawat; Sonik Anto; Vinay Sahu; C. P. Singh; Anzar Ahmad Khuroo (Environmental Monitoring and Assessment, 2025)

Drought induced alterations in the physiological traits of novel citrus hybrids - Anagha Pilathottathil Kuzhiyil; Radha Mohan Sharma; Anil Kumar Dubey; Amit Kumar Goswami; Sudhir Kumar; Shailendra Jha; Amrender Kumar; Deepak Yadav; Mude Ramya Sree (Plant Physiology Reports, 2025)

ARRDC3, a novel α-arrestin, modulates WSSV replication and AHPND pathogenesis in Litopeneaus vannamei - Ramya Kumar; Brandon Rafael de Jesús Castillo-Corea; Shih-Shun Lin; Chien-Kang Huang; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Exploring the toxicity of chromium on aquatic ecosystems: a comprehensive assessment of growth, physiological responses, genotoxicity, and histological alterations in Etroplus suratensis (Bloch, 1790) juveniles - Ramya V.; Madhuri S. Pathak; Kapil Sukhdhane; Kishore Kumar Krishnani; Thongam Ibemcha Chanu; Harini G.; Harshavarthini M. (Aquaculture International, 2024)

Powdery mildew pathogen [Erysiphe necator (Schw.) Burrill.] induced physiological and biochemical alterations in leaf tissue of grapevines (Vitis spp.) - M. Ramya Sree; Sanjay K. Singh; Jai Prakash; Chavlesh Kumar; Aundy Kumar; Gyan P. Mishra; Amitha Mithra Sevanthi; H.S. Sreekanth; Ediga Amala (Physiological and Molecular Plant Pathology, 2024)

Genetic Nature and Role of Environment in Sex Expression and Phenological Characters of Pistillate Lines in Castor (Ricinus communis L.) - T. Manjunatha; K. T. Ramya; C. Lavanya; C. Sarada; S. Senthilvel; M. Yamanura; C. J. Patel; A. M. Patel; Mukesh Kumar Patel; R. Madariya; Praduman Yadav (Genetic Resources and Crop Evolution, 2024)

Enhanced response of WO3 thin film through Ag loading towards room temperature hydrogen gas sensor - Ramya Barathy T; P.V. Karthik Yadav; Anibrata Mondal; Karthickraja Ramakrishnan; Jayaramudu Jarugala; Chunli Liu; Y. Ashok Kumar Reddy (Chemosphere, 2024)

Corrigendum to “Food waste-derived black soldier fly (Hermetia illucens) larval resource recovery: A circular bioeconomy approach” Process Saf. Environ. Prot. 184 (2024) 170–189 - Abirami Ramu Ganesan; Kannan Mohan; Sabariswaran Kandasamy; Ramya Preethi Surendran; Ragavendhar Kumar; Durairaj Karthick Rajan; Jayakumar Rajarajeswaran (Process Safety and Environmental Protection, 2024)

Food waste-derived black soldier fly (Hermetia illucens) larval resource recovery: A circular bioeconomy approach - Abirami Ramu Ganesan; Kannan Mohan; Sabariswaran Kandasamy; Ramya Preethi Surendran; Ragavendhar Kumar; Durairaj Karthick Rajan; Jayakumar Rajarajeswaran (Process Safety and Environmental Protection, 2024)

Genetic characterization of minor carp (Labeo gonius) from Indian rivers revealed through mitochondrial ATPase 6/8 and D-loop region analysis: implications for conservation and management - Suvra Roy; Bijay Kumar Behera; Ramya V. L.; Ajay Kumar Rout; Vikash Kumar; Pranay Kumar Parida; Asim Kumar Jana; Pronob Das; Dharmendra Kumar Meena; Dibakar Bhakta; Absar Alam; Basanta Kumar Das; et al. (Frontiers in Marine Science, 2024)
India is the habitat of many freshwater fish species that make a significant contribution to endemism. However, the native species population is declining at a very fast rate due to pollution, habitat loss or degradation, new species introduction, hydrologic alterations, and overfishing. The minor carp, Labeo gonius , is one of the important fish species in the Indian river systems and holds enormous potential in culture fisheries. Therefore, the precise status of population structure is a prerequisite for the management of the species. In the present study, we assessed the potential of mtDNA ATPase 6/8 and D-loop regions as markers to determine the genetic diversity and phylogeography of L. gonius from Indian rivers. We have selected five major Indian rivers for investigation which could represent geographically distant populations of the studied fish. A total of 210 ATPase 6/8 sequences (842 bp) and 203 D-loop region sequences (683 bp) of L. gonius from the five major Indian rivers were submitted to NCBI. Results revealed that ATPase 6/8 has 17 haplotypes and 70 polymorphic sites with an overall haplotype diversity of 0.560 ± 0.036 and nucleotide diversity of 0.00347 ± 0.00. Furthermore, D-loop analysis revealed 58 haplotypes, 67 polymorphic sites, 0.954 ± 0.006 overall haplotype diversity, and 0.01914 ± 0.00 nucleotide diversity. The hierarchical AMOVA analysis indicated that a high proportion of the genetic variation (76.46% and 70.22% for the D-loop and ATPase 6/8 regions, respectively) was attributed to among-population variation under gene pool-1 (considering all the stocks from Ganga, Brahmaputra, Teesta, Narmada, and Mahanadi as a single pool). Furthermore, in gene pool-2, samples were divided into two groups: group 1 (Himalayan rivers)—Ganga, Brahmaputra, and Teesta; and group 2 (peninsular rivers)—Narmada and Mahanadi. Genetic variations in the D-loop and ATPase 6/8 regions were found among populations within groups at 70.65% and 53.48%, respectively. Haplotype network analysis revealed that there were significant differences in distributions and frequencies. The observed unique haplotypes might be useful for differentiating the stocks. In brief, the present study suggested that the D-loop and ATPase 6/8 regions are potential markers and represent a significant contribution to the genetic characterization of the minor carp L. gonius from major Indian rivers. Moreover, the L. gonius population along the east coast especially in the Himalayan rivers (Ganga, Brahmaputra, and Teesta river basin) is found to be genetically more diverse. The results would provide a scientific basis for the assessment of fisheries resources and management of this important species.

Monitoring the quality of ground water in pipelines using deep neural network model - M. Ashok Kumar; N. Srinivas; P. Ramya; Neha Ahlawat; Jaya Sharma; Franklin Vinod (Groundwater for Sustainable Development, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Cyclometalated Ir(III) theranostic molecular probe enabled mitochondria targeted fluorescence-SERS-guided phototherapy in breast cancer cells - Chandana Reghukumar; Shanmughan Shamjith; Vishnu Priya Murali; Pilankatta K. Ramya; Kokkuvayil Vasu Radhakrishnan; Kaustabh Kumar Maiti (Journal of Photochemistry and Photobiology B: Biology, 2024)

Spatial distribution and optimum sample size for monitoring of water lily aphid Rhopalosiphum nymphaeae (L.) in Makhana Euryale ferox Salisb - Vinod K. Padala; N Ramya; Manoj Kumar; S Rajna; Mandla Rajashekhar; YN Venkatesh; SM Raut; Subhash Chander; IS Singh; Mohd. Monobrullah (International Journal of Tropical Insect Science, 2023)

Bifunctional electrode of bismuth tungsten for electrochemical sensing applications - Abdullah K. Alanazi; P. Senthil Kumar; M. Ramya; Hala M. Abo-Dief; Gayathri Rangasamy (Chemosphere, 2023)

Oligodendroglia Confer Neuroprotection to NSC-34 Motor Neuronal Cells Against the Toxic Insults of Cerebrospinal Fluid from Sporadic Amyotrophic Lateral Sclerosis Patients - V. Ramya; Nisha Sarkar; Savita Bhagat; Raj Kumar Pradhan; Anu Mary Varghese; Atchayaram Nalini; Talakad N. Sathyaprabha; Trichur R. Raju; K. Vijayalakshmi (Molecular Neurobiology, 2023)

Resilience and probiotic interventions to prevent and recover from shrimp gut dysbiosis - Ramya Kumar; Mei-Ying Huang; Chih-Ling Chen; Han-Ching Wang; Hsiao-Pei Lu (Fish & Shellfish Immunology, 2023)

Multivariate approach to link phytoplankton dynamics to environmental variations in a large tropical reservoir - Jesna Parakkandi; Vijayakumar Leela Ramya; Ajoy Saha; Sibinamol Salim; Preetha Panikkar; Karthikeyan Mani; Vijaykumar Muttanahalli Eregowda; Uttam Kumar Sarkar; Basanta Kumar Das (Arabian Journal of Geosciences, 2023)

Cryostress induces fragmentation and alters the abundance of sperm transcripts associated with fertilizing competence and reproductive processes in buffalo - Sellappan Selvaraju; Laxman Ramya; Divakar Swathi; Santhanahalli Siddalingappa Archana; Maharajan Lavanya; Balaganur Krishnappa; Bala Krishnan Binsila; Ajit Singh Mahla; Arunachalam Arangasamy; Jerome Andonissamy; Pradeep Kumar; Rakesh Kumar Sharma (Cell and Tissue Research, 2023)

Characterization of fine particulate matter water-soluble inorganic ions and estimation of aerosol acidity at three COALESCE network sites — Mysuru, Bhopal, and Mesra — in India - Abisheg Dhandapani; Jawed Iqbal; Radhakrishnan Naresh Kumar; Ankur Bhardwaj; Deeksha Shukla; Ramya Sunder Raman; Sanyasihally Vasanthkumar Laxmi Prasad; Boohalli Mahadevappa Sadashiva Murthy (Environmental Science and Pollution Research, 2023)

Pollution characteristics and ecological risks of trace elements in PM2.5 over three COALESCE network sites - Bhopal, Mesra, and Mysuru, India - Diksha Haswani; Ramya Sunder Raman; Kajal Yadav; Abisheg Dhandapani; Jawed Iqbal; R. Naresh Kumar; S.V. Laxmi Prasad; Adi Yogesh; Sadashiva Murthy B.M.; K.S. Lokesh (Chemosphere, 2023)

Preparation and characterization of a novel cobalt-substitution cadmium aluminate spinel for the photodegradation of azo dye pollutants - G. Rajesh; P. Senthil Kumar; S. Akilandeswari; Gayathri Rangasamy; S. Lohita; V. Uma Shankar; M. Ramya; K. Thirumalai (Chemosphere, 2023)

Fabrication of an effectual, stable and reusable Mg-doped CdAl2O4 nanoparticles for photodegradation of toxic pollutants under visible light illumination - S. Mahalaxmi; G. Rajesh; P. Senthil Kumar; S. Akilandeswari; M. Arul Joshua; V. Uma Shankar; M. Ramya; K. Thirumalai; Gayathri Rangasamy (Chemosphere, 2023)

Strategies for ameliorating the photodegradation efficiency of Mn-doped CdAl2O4 nanoparticles for the toxic dyes under visible light illumination - G. Rajesh; P. Senthil Kumar; S. Akilandeswari; Gayathri Rangasamy; S. Lohita; V. Uma Shankar; M. Ramya; K. Nirmala; K. Thirumalai (Chemosphere, 2023)

A synergistic consequence of catalyst dosage, pH solution and reactive species of Fe-doped CdAl2O4 nanoparticles on the degradation of toxic environmental pollutants - G. Rajesh; P. Senthil Kumar; S. Akilandeswari; Gayathri Rangasamy; Aindrila Mandal; V. Uma Shankar; M. Ramya; K. Nirmala; K. Thirumalai (Chemosphere, 2023)

Experimental investigation of the electrochemical detection of sulfamethoxazole using copper oxide-MoS2 modified glassy carbon electrodes - M. Ramya; P. Senthil Kumar; Gayathri Rangasamy; V. Uma Shankar; G. Rajesh; K. Nirmala (Environmental Research, 2023)

Preparation and Evaluation of Silver Nanoparticles Embedded in Muntingia calabura Leaf Extract to Cure White Piedra - S. Vignesh Kumar; T. Ramya Sri; N. Prakash; E. Muthusankar (Journal of Pharmaceutical Innovation, 2022)

A rare occurrence of multidrug-resistant environmental Acinetobacter baumannii strains from the soil of Mangaluru, India - Sarika Suresh; Vankadari Aditya; Vijaya Kumar Deekshit; Radhakrishna Manipura; Ramya Premanath (Archives of Microbiology, 2022)

Computational screening of natural compounds from Salvia plebeia R. Br. for inhibition of SARS-CoV-2 main protease - Afraa Aqeel Zackria; Ramya Pattabiraman; T. P. Krishna Murthy; S. Birendra Kumar; Blessy Baby Mathew; Vinai George Biju (Vegetos, 2022)

Non-thermal plasmas for disease control and abiotic stress management in plants - Susmita C.; S. P. Jeevan Kumar; Anjani Devi Chintagunta; Eric Lichtfouse; Bhojaraj Naik; Ramya P.; Kalyani Kumari; Sanjay Kumar (Environmental Chemistry Letters, 2022)

The regulation of shrimp metabolism by the white spot syndrome virus (WSSV) - Ramya Kumar; Jiun‐Yan Huang; Yen‐Siong Ng; Cong‐Yan Chen; Han‐Ching Wang (Reviews in Aquaculture, 2022)
For more than three decades, infectious diseases have been one of the major causes of economic losses in the global shrimp industry. One of the deadliest of the shrimp pathogens is white spot syndrome virus (WSSV), which causes mass mortality in farmed shrimp. Various aspects of WSSV pathogenicity have been studied, but in this review, we will focus only on one of them, namely metabolic reprogramming. WSSV’s modulation of host metabolism affects glycolysis, the tricarboxylic acid (TCA) cycle, glutaminolysis and lipid metabolism. Several signaling pathways are involved in this regulation, including JAK‐STAT, PI3K‐AKT‐mTOR, MAPK and Ras‐Raf‐MEK, with the PI3K‐Akt‐mTOR pathway in particular playing a critical role in activating the WSSV‐induced Warburg effect. Taken together, these changes benefit the virus by facilitating WSSV replication. In this review, we summarize current knowledge regarding the metabolism‐related aspects of WSSV pathogenesis, and discuss the mechanisms by which this virus reprograms its host's metabolic pathways. A deeper understanding of these pathways, key metabolic enzymes and signaling mechanisms is potentially important for the development of effective anti‐WSSV strategies.

Evolution and co-evolution: insights into the divergence of plant heat shock factor genes - Ramya Parakkunnel; K Bhojaraja Naik; C Susmita; Vanishree Girimalla; K Udaya Bhaskar; KV Sripathy; CS Shantharaja; S Aravindan; Sanjay Kumar; Suman Lakhanpaul; KV Bhat (Physiology and Molecular Biology of Plants, 2022)

Application of “OTSU”—an image segmentation method for differentiation of snow and ice regions of glaciers and assessment of mass budget in Chandra basin, Western Himalaya using Remote Sensing and GIS techniques - Vinay Kumar Gaddam; Ramya Boddapati; Tanooj Kumar; Anil V. Kulkarni; Helgi Bjornsson (Environmental Monitoring and Assessment, 2022)

Nanotechnology-based approaches applied to nutraceuticals - Akanksha R. Singh; Prasanna Kumar Desu; Ramya Krishna Nakkala; Vanitha Kondi; Sushma Devi; Mohammad Sarwar Alam; Hinna Hamid; Rajani B. Athawale; Prashant Kesharwani (Drug Delivery and Translational Research, 2022)

Modeling impacts of invasive sharp tooth African catfish Clarias gariepinus (Burchell 1822) and Mozambique tilapia Oreochromis mossambicus (Peters, 1852) on the ecosystem of a tropical reservoir ecosystem in India - Mohamed Feroz Khan; Preetha Panikkar; Sibina Mol Salim; Ramya Vijayakumar Leela; Uttam Kumar Sarkar; Basanta Kumar Das; Vijayakumar Muttenahalli Eregowda (Environmental Science and Pollution Research, 2021)

Stock structure analysis of the endemic fish, Barbodes carnaticus (Jerdon 1849), for conservation in a biodiversity hotspot - Vijayakumar Leela Ramya; Bijay Kumar Behera; Basanta Kumar Das; Gopal Krishna; Annam Pavankumar; Mujahid Khan Pathan (Environmental Science and Pollution Research, 2021)

Association between RAD51, XRCC2 and XRCC3 gene polymorphisms and risk of ovarian cancer: a case control and an in silico study - G. Gowtham Kumar; Solomon Franklin Durairaj Paul; Jovita Martin; M. Manickavasagam; Shirley Sundersingh; Nalini Ganesan; R. Ramya; G. Usha Rani; Francis Andrea Mary (Molecular Biology Reports, 2021)

Habitat based fish assemblage and distribution pattern in a large reservoir of peninsular India - Vijayakumar Leela Ramya; Jesna Parakkandi; Ajoy Saha; Sibina-Mol Salim; Preetha Panikkar; Uttam Kumar Sarkar; Vijaykumar Muttanahalli Eregowda; Karthikeyan Mani; Basanta Kumar Das (Arabian Journal of Geosciences, 2021)

Two-year record of carbonaceous fraction in ambient PM2.5 over a forested location in central India: temporal characteristics and estimation of secondary organic carbon - Shilpi Samiksha; Samresh Kumar; Ramya Sunder Raman (Air Quality, Atmosphere & Health, 2021)

Acute hepatopancreatic necrosis disease in penaeid shrimp - Ramya Kumar; Tze Hann Ng; Han‐Ching Wang (Reviews in Aquaculture, 2020)
Asian countries are the major producers of cultured Penaeid shrimps such as Penaeus monodon and Penaeus ( Litopenaeus ) vannamei . In recent years, shrimp production has declined due to the emergence of a bacterial disease called acute hepatopancreatic necrosis disease (AHPND). This disease is mainly caused by Vibrio parahaemolyticus , but other Vibrio species are also known to cause AHPND in shrimps. Here, in addition to reviewing recent developments in the field of AHPND diagnosis, host responses to AHPND, the role of microbiota during AHPND infection and the current treatment options for AHPND, we also describe a model of AHPND pathogenesis.

Detection of microcystin producing cyanobacteria in Spirulina dietary supplements using multiplex HRM quantitative PCR - Kamath Mukund Manali; Rex Arunraj; Thangarathinam Kumar; Mohandass Ramya (Journal of Applied Phycology, 2017)

Evaluation of Mass Transfer Kinetics for Osmotic Dehydration of Oyster Mushrooms (Pleurotus sajor-caju) in Salt-sugar Solution - H. G. Ramya; Satish Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Diesel biodegradation capacities of indigenous bacterial species isolated from diesel contaminated soil - Nandhini Palanisamy; Jayaprakash Ramya; Srilakshman Kumar; NS Vasanthi; Preethy Chandran; Sudheer Khan (Journal of Environmental Health Science and Engineering, 2014)
Petroleum based products are the major source of energy for industries and daily life. Leaks and accidental spills occur regularly during the exploration, production, refining, transport, and storage of petroleum and petroleum products. In the present study we isolated the bacteria from diesel contaminated soil and screened them for diesel biodegradation capacity. One monoculture isolate identified by 16S rRNA gene sequence analysis to be Acinetobacter baumannii was further studied for diesel oil biodegradation. The effects of various culture parameters (pH, temperature, NaCl concentrations, initial hydrocarbon concentration, initial inoculum size, role of chemical surfactant, and role of carbon and nitrogen sources) on biodegradation of diesel oil were evaluated. Optimal diesel oil biodegradation by A. baumanii occurred at initial pH 7, 35°C and initial hydrocarbon concentration at 4%. The biodegradation products under optimal cultural conditions were analyzed by GC-MS. The present study suggests that A. baumannii can be used for effective degradation of diesel oil from industrial effluents contaminated with diesel oil.

Molecular cloning, characterization and functional assessment of the myosin light polypeptide chain 2 (mylz2) promoter of farmed carp, Labeo rohita - Ramya Mohanta; Pallipuram Jayasankar; Kanta Das Mahapatra; Jatindra Nath Saha; Hirak Kumar Barman (Transgenic Research, 2014)

Gene structure and identification of minimal promoter of Pou2 expressed in spermatogonial cells of rohu carp, Labeo rohita - Chinmayee Mohapatra; Swagat Kumar Patra; Rudra Prasanna Panda; Ramya Mohanta; Ashis Saha; Jatindra Nath Saha; Kanta Das Mahapatra; Pallipuram Jayasankar; Hirak Kumar Barman (Molecular Biology Reports, 2014)

Synthesis, anticancer, and molecular docking studies of pyranone derivatives - P. M. Gurubasavaraja Swamy; B. Ramya Sri; D. Giles; B. V. Shashidhar; Amit Kumar Das; Y. S. Agasimundin (Medicinal Chemistry Research, 2013)